2015
DOI: 10.1177/2053168015573348
|View full text |Cite
|
Sign up to set email alerts
|

Vote choice and legacies of violence: evidence from the 2014 Colombian presidential elections

Abstract: Elections are regularly held in countries facing ongoing civil conflicts, including in India, Iraq, Nigeria, the Philippines, and Ukraine. Citizens frequently go to the polls having endured years of violence between armed groups and governments. A growing literature questions how violence conditions voters' support for incumbents versus challengers, and for hawks versus doves. We analyze this relationship in the context of the 2014 presidential election in Colombia, an election defined by candidates' positions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 32 publications
3
34
1
4
Order By: Relevance
“…21 The analysis also shows that other factors had an impact on support for the peace agreement. First, and in line with previous findings (Fergusson and Molina 2016;Liendo and Braithwaite 2018;Weintraub et al 2015), municipalities with higher levels of support for Santos in the 2014 presidential elections were more prone to vote yes in the referendum (p < 0.01). This was to be expected, as both the 2014 elections and the 2016 referendum were marked by a strong cleavage over the peace process, with Santos as the "pro-peace" candidate.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…21 The analysis also shows that other factors had an impact on support for the peace agreement. First, and in line with previous findings (Fergusson and Molina 2016;Liendo and Braithwaite 2018;Weintraub et al 2015), municipalities with higher levels of support for Santos in the 2014 presidential elections were more prone to vote yes in the referendum (p < 0.01). This was to be expected, as both the 2014 elections and the 2016 referendum were marked by a strong cleavage over the peace process, with Santos as the "pro-peace" candidate.…”
Section: Resultssupporting
confidence: 89%
“…If we look beyond the referendum, evidence is equally conflicting. For example, analyzing the 2014 presidential elections, Weintraub et al (2015) found that Juan Manuel Santos-the pro-peace candidate-performed well in communities with moderate levels of violence but poorly in communities with very high and low levels. Relying on 2014 AmericasBarometer survey data, which included a question about support for the then-ongoing peace process, Liendo and Braithwaite (2018) found that existing political preferences overwhelmingly drove attitudes toward the peace process with the FARC, not experiences of violence (see also Brodzinsky 2016).…”
Section: Exposure To Violence and Attitudes Toward Peacementioning
confidence: 99%
See 1 more Smart Citation
“… 1. However, several other studies find that pro-peace (“weary”) or more militant (“angry”) responses are both possible depending upon other factors. In Colombia’s 2014 election, Weintraub, Vargas, and Flores (2015) finds “an inverted-U relationship” between exposure to violence by insurgents and support for the pro-peace candidate. Huddy et al (2005) finds that individuals who responded to the 9/11 terror attack with anxiety appear to be more pro-peace, while those who respond with heightened threat perception appear to be more bellicose. …”
mentioning
confidence: 99%
“…Finally, Dell & Querubin (2016a) find that US-led counterinsurgency bombings in Vietnam had a negative effect on local governance, 9 while Dell & Querubin (2016b) show that historical norms of governance -whether a village had a bureaucratic state or a patron-client state more than a hundred years ago -continues to shape living standards today. A parallel literature on violence offers theoretical arguments and sophisticated empirical tests regarding the long-term effects of violence at both the individual and community levels, showing how violence affects voting behavior (Berrebi & Klor, 2006;Montalvo, 2010;Getmansky & Zeitzoff, 2014;Weintraub et al, 2015), community participation (Bateson, 2013), civilian mobilization (Schubiger, 2013;Osorio et al, 2017), and attitudes towards former perpetrators across generations (Balcells, 2012;Lupu & Peisakhin, 2017). We draw on these strands of the literature to motivate a focus on a diverse set of factors related to state consolidation.…”
Section: Forced Disappearances and State Consolidationmentioning
confidence: 99%